COMPREHENSIVE ANALYSIS OF THE EFFECTIVENESS OF HERBAL REMEDIES IN TREATING DISEASES. - 1Mohammed Makki Sughayyir, ‏2Ibraheem Qasim Bagawi, 3Nouf Eid Ghanem Alerwi, 4Ahmed Ibrahim Alzahrani, 5Mohammed Mana Misfer Al Juraib, 6Meshaal Hussain Saleh Bani Humayyim, 7Khaled Hussein Saleh Bani Hamim, 8Sana Mohammed Mubarak (Chelonian Research Foundation, 2022)
Herbs and supplements have increased significantly over the past three decades. At least 80% of the world's population relies on them for some form of treatment. Although these medicinal products are effective, and the benefits of many herbal products have been demonstrated, many are untested, not used correctly, and are not authentic. The result is a need for more understanding of the drug's mechanism of action, potential side effects, contraindications, interactions with existing foods, and conventional science supporting the safety and use of this drug. As safety remains an important issue in the use of herbs, appropriate regulatory bodies must ensure the safety and quality of all herbs and protect public health. This review discusses the major toxicity and safety issues arising from the use of herbal medicines and highlights some important issues regarding their safety. Keywords: medicinal plants, harmful drugs, safety, problems, public health.